Extension for Community Healthcare Outcomes-Palliative Care in Africa and Quality of Life, Symptoms, Patient Experience, and Caregiver Distress Among Patients With Cancer - Sriram Yennurajalingam; Olaitan Soyannwo; John Weru; Edwina Beryl VND Addo Opare-Lokko; Henriette Burger; Esther Nafulah; Oladayo Aikomo; Adeniyi Adenipekun; Irene Botchway; Mary Ocansey; Jayita Deodhar; Jianliang Dai; et al. (JCO Global Oncology)
PURPOSEIn this study, we aimed to evaluate the association between the Extension for Community Healthcare Outcomes-Palliative Care (ECHO-PC; ECHO Model–Based comprehensive educational and telementoring intervention) for health care professionals (HCPs) and change in patient-reported quality-of-life (QOL; Functional Assessment of Cancer Therapy-General [FACT-G]) among patients with advanced cancer. We also examined the association between ECHO-PC and changes in symptom distress (Edmonton Symptom Assessment Scale [ESAS]), patient experience and satisfaction, and caregiver distress scores.METHODSECHO-PC Clinic sessions were conducted twice a month for 1 year by an interdisciplinary team of PC clinicians at the MD Anderson Cancer Center, with participation of experts in PC in sub-Saharan Africa, using standardized curriculum on the basis of PC needs in the region. Study participants included palliative HCPs from ECHO participating programs in Kenya, Nigeria, Ghana, and South Africa. HCPs, their patients, and caregivers were assessed at baseline, 3, 6, 9, and 12 months of the study for QOL (FACT-G), ESAS-Symptom Distress Score (prorated) (SDS), patient experience, satisfaction (FAMCARE-P-16-patient), and caregiver distress (FAMCARE-caregiver).RESULTSTwo hundred seventy patients completed the assessments. Fifty-eight percent was female, the mean age was 56 years, and most common cancer type was breast cancer (24.3%). Multivariate generalized linear mixed model analysis found that ECHO-PC intervention was associated with significant improvement in QOL and symptom distress (FACT-G total score, P = .0433; FACT-G physical well-being, P < .013; FACT-G emotional well-being, P = .0232, and ESAS-SDS, P < .0001). No significant changes were found in patient experience, satisfaction, and caregiver distress scores.CONCLUSIONOur preliminary study found that the ECHO-PC intervention was significantly associated with improvement in patient outcomes including QOL and symptom distress scores. Further studies are needed.